PENINGKATAN PERTUMBUHAN EKONOMI DAN PENDAPATAN ASLI DAERAH DAN DANA ALOKASI BELANJA DAERAH PROVINSI SUMATERA UTARA BERBASISKAN SMART EDUKASI - Feby Milanie; Muammar Khaddafi; Adam Afiezan (Edukasi Islami : Jurnal Pendidikan Islam, 2021)
This study aims 1) to determine how much influence Economic Growth, Regional Original Income, and General Allocation Funds partially have a significant effect on Capital Expenditures in Regencies/Cities in North Sumatra. 2) to find out how much influence Economic Growth, Regional Original Income, and General Allocation Funds simultaneously have a significant effect on Capital Expenditures in Regencies/Cities in North Sumatra. This study uses the associative/quantitative method with the influence of economic growth, local revenue, and general allocation funds with a mathematical approach to answering the problem formulation. The results of the t-count study indicate that the variables of economic growth and general allocation funds have a partial effect on capital expenditures, while local revenue does not partially affect capital expenditures. The results of the f-count study indicate that the variables of economic growth, regional original income, and general allocation funds have a simultaneous effect on capital expenditure.